O financiamento do BNDES gera valor para o acionista de empresas financiadas? - Bellegard, Fabio Glock (2016)
Through simultaneous equations and based on the Value Relevance Literature, this study discusses the relevance of BNDES loans to explain the stock prices of companies listed in BOVESPA. The simultaneous equations model allows exogenous variations on the credit offer by BNDES. Such variations permit the identification of the model that defines stock prices as function of BNDES loans as well as control variables. Results found do not confirm that the presence of BNDEs loans is significant to explain stock prices.